Interface modification of glass fibre–polyester composite–composite joints using peel plies. (June 2015) - Kanerva, M.; Sarlin, E.; Hoikkanen, M.; Rämö, K.; Saarela, O.; Vuorinen, J.
Abstract: This work includes an investigation of six different surface treatments for joining composites by overlamination. The durability of the pre-treated glass fibre-unsaturated polyester composite joints is investigated accounting for a 200-day water immersion at 64±1 °C. Degradation due to accelerated aging, by water and elevated temperature, is analysed using Fourier transform infrared spectroscopy (FTIR), water absorption measurement, tensile testing and a systematic sequence of four different fracture test methods. Based on the fracture tests, the mechanical abrading treatment outperformed all other treatments yet suffered an adverse effect due to the combined moisture and elevated temperature. We observed irreversible chemical degradation in the bulk composite in terms of permanent 2.3% weight loss. The softening and plasticization of the polyester matrix seemed to have played a fundamental role in the rupture of adhesion at the peel ply and tear ply pre-treated overlamination interfaces. However, the adhesion loss was partly reversible and it was concluded to signify the domination of mechanical interlocking at peel ply and tear ply modified interfaces.